2020
DOI: 10.1002/aqc.3281
|View full text |Cite
|
Sign up to set email alerts
|

Predictive modelling of mesophotic habitats in the north‐western Gulf of Mexico

Abstract: 1. Effective management of marine resources requires an understanding of the spatial distribution of biologically important communities.2. The north-western Gulf of Mexico contains diverse marine ecosystems at a large range of depths and geographic settings. To better understand the distribution of these marine habitats across large geographic areas under consideration for marine sanctuary status, presence-only predictive modelling was used.3. Results confirmed that local geographic characteristics can accurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The highest gridding resolution of bathymetry data determined the finest spatial scale (2 m). The appropriate broad scale was determined using Dragut's Estimation of Scale Parameter (ESP) Tool (Drǎguţ et al 2010), where a decline in Rate of Change of Local Variance (ROC-LV) curves was observed at a resolution of 25 m. Derivatives were also calculated at 10 m resolution to account for intermediate-scale effects and following resolutions used in other mesophotic reef studies (Costa et al 2015;Sterne et al 2020). Although variables at multiple scales exhibited collinearity, these were retained to account for possible multiscale effects of predictors on assemblage occurrence and distribution.…”
Section: Environmental Predictorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest gridding resolution of bathymetry data determined the finest spatial scale (2 m). The appropriate broad scale was determined using Dragut's Estimation of Scale Parameter (ESP) Tool (Drǎguţ et al 2010), where a decline in Rate of Change of Local Variance (ROC-LV) curves was observed at a resolution of 25 m. Derivatives were also calculated at 10 m resolution to account for intermediate-scale effects and following resolutions used in other mesophotic reef studies (Costa et al 2015;Sterne et al 2020). Although variables at multiple scales exhibited collinearity, these were retained to account for possible multiscale effects of predictors on assemblage occurrence and distribution.…”
Section: Environmental Predictorsmentioning
confidence: 99%
“…Assemblage 2 contained both zooxanthellate and azooxanthellate species and is therefore in part associated with depths where sufficient light penetrates to enable photosynthesis. Assemblage 2 was also associated with slope and curvature which mediate hydrodynamic properties of water flow past the reef system, influencing food availability for heterotrophic suspension-feeding organisms (Locker et al 2010;Bridge et al 2011b;Sterne et al 2020). Increased slope values may also shield taxa characterized by flattened morphologies found in assemblage 2 from heavy sedimentation (Ohlhorst and Liddell 1988;Kahng et al 2010).…”
Section: Drivers and Distribution Of Mesophotic Assemblagesmentioning
confidence: 99%
“…Notably, MaxEnt, in accordance with the principle of maximum entropy [19,22,26], is frequently regarded as outperforming other species distribution models (SDMs) due to its strong toleration and precise forecasting in many model intercomparisons [27][28][29]. Researchers worldwide in the last decade have achieved significant success in applying species distribution models to issues such as protecting the diversity of rare animals and plants [30][31][32][33], estimating the dangers of invasive species [34][35][36], protecting marine ecosystem [37,38], predicting disaster distribution [39], and disease propagation [40,41], employing the MaxEnt model.…”
Section: Introductionmentioning
confidence: 99%
“…Many model intercomparison studies have reported that the MaxEnt model, which is based on the principle of maximum entropy 23 , 26 , 30 , typically outperforms other species distribution models (SDMs) in terms of high tolerance and high predictive accuracy 31 33 . Over the past 10 years, worldwide research teams have achieved excellent results in the study of rare animal and plant diversity protection 34 – 38 , invasive species risk prediction 39 41 , marine ecosystem protection 42 , 43 , disaster distribution prediction 44 , and disease propagation 45 , 46 using the MaxEnt model. Zhang et al 47 found that the area of suitable range of Cinnamomum camphora (L.) Presl will increase and continue to move to the northwest of China under future climate change scenarios.…”
Section: Introductionmentioning
confidence: 99%